Intelligent Tutoring Systems 10th International Conference, ITS 2010, Pittsburgh, PA, USA, June 14-18, 2010, Proceedings, Part I - Aleven, Vincent; Kay, Judy.; Mostow, Jack.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The books (LNCS 6094 and 6095) constitute the refereed proceedings of the 10th International Conference on Intelligent Tutoring Systems, ITS 2010, held in Pittsburgh, PA, USA, in June 2010. The 61 revised full papers, 5 invited talks, and 58 short papers presented were carefully viewed and selected from 186 submissions. The papers are organized in topical sections on educational data mining, natural language interaction; ITS in Ill-defined domains; inquiry learning, collaborative and group learning; intelligent games; gaming the system; pedagogical strategies; affect; games and augmented reality; pedagogical agents, learning companions, and teachable agents; intelligent tutoring and scaffolding; metacognition; and authoring tools and theoretical synthesis.
Invited Talks -- Can Research-Based Technology Change School-Based Learning? Perspectives from Singapore -- Modeling Emotion and Its Expression -- Active Learning in Technology-Enhanced Environments: On Sensible and Less Sensible Conceptions of (3z(BActive(3y (Band Their Instructional Consequences -- Riding the Third Wave -- Social and Caring Tutors -- Educational Data Mining 1 -- Predicting Correctness of Problem Solving in ITS with a Temporal Collaborative Filtering Approach -- Detecting the Moment of Learning -- Comparing Knowledge Tracing and Performance Factor Analysis by Using Multiple Model Fitting Procedures -- Natural Language Interaction 1 -- Automatic Question Generation for Literature Review Writing Support -- Characterizing the Effectiveness of Tutorial Dialogue with Hidden Markov Models -- Exploiting Predictable Response Training to Improve Automatic Recognition of Children$1 (Bs Spoken Responses -- ITS in Ill-Defined Domains -- Leveraging a Domain Ontology to Increase the Quality of Feedback in an Intelligent Tutoring System -- Modeling Long Term Learning of Generic Skills -- Eliciting Informative Feedback in Peer Review: Importance of Problem-Specific Scaffolding -- Inquiry Learning -- Layered Development and Evaluation for Intelligent Support in Exploratory Environments: The Case of Microworlds -- The Invention Lab: Using a Hybrid of Model Tracing and Constraint-Based Modeling to Offer Intelligent Support in Inquiry Environments -- Discovering and Recognizing Student Interaction Patterns in Exploratory Learning Environments -- Collaborative and Group Learning 1 -- Lesson Study Communities on Web to Support Teacher Collaboration for Professional Development -- Using Problem-Solving Context to Assess Help Quality in Computer-Mediated Peer Tutoring -- Socially Capable Conversational Tutors Can Be Effective in Collaborative Learning Situations -- Intelligent Games 1 -- Facial Expressions and Politeness Effect in Foreign Language Training System -- Intercultural Negotiation with Virtual Humans: The Effect of Social Goals on Gameplay and Learning -- Gaming the System -- An Analysis of Gaming Behaviors in an Intelligent Tutoring System -- The Fine-Grained Impact of Gaming (?) on Learning -- Squeezing Out Gaming Behavior in a Dialog-Based ITS -- Pedagogical Strategies 1 -- Analogies, Explanations, and Practice: Examining How Task Types Affect Second Language Grammar Learning -- Do Micro-Level Tutorial Decisions Matter: Applying Reinforcement Learning to Induce Pedagogical Tutorial Tactics -- Examining the Role of Gestures in Expert Tutoring -- Affect 1 -- A Time for Emoting: When Affect-Sensitivity Is and Isn$1 (Bt Effective at Promoting Deep Learning -- The Affective and Learning Profiles of Students Using an Intelligent Tutoring System for Algebra -- The Impact of System Feedback on Learners$1 (BAffective and Physiological States -- Games and Augmented Reality -- Investigating the Relationship between Presence and Learning in a Serious Game -- Developing Empirically Based Student Personality Profiles for Affective Feedback Models -- Evaluating the Usability of an Augmented Reality Based Educational Application -- Pedagogical Agents, Learning Companions, and Teachable Agents -- What Do Children Favor as Embodied Pedagogical Agents? -- Learning by Teaching SimStudent: Technical Accomplishments and an Initial Use with Students -- The Effect of Motivational Learning Companions on Low Achieving Students and Students with Disabilities -- Intelligent Tutoring and Scaffolding 1 -- Use of a Medical ITS Improves Reporting Performance among Community Pathologists -- Hints: Is It Better to Give or Wait to Be Asked? -- Error-Flagging Support for Testing and Its Effect on Adaptation -- Metacognition -- Emotions and Motivation on Performance during Multimedia Learning: How Do I Feel and Why Do I Care? -- Metacognition and Learning in Spoken Dialogue Computer Tutoring -- A Self-regulator for Navigational Learning in Hyperspace -- Pedagogical Strategies 2 -- How Adaptive Is an Expert Human Tutor? -- Blocked versus Interleaved Practice with Multiple Representations in an Intelligent Tutoring System for Fractions -- Improving Math Learning through Intelligent Tutoring and Basic Skills Training.s
Keywords: Computer science; Multimedia systems; Artificial intelligence; Text processing (Computer science; Social sciences -- Data processing; Education; Computer Science; Computers and Education; User Interfaces and Human Computer Interaction; Multimedia Information Systems; Computer Appl. in Social and Behavioral Sciences; Document Preparation and Text Processing; Artificial Intelligence (incl. Robotics).